Reengineering of technological business processes of a generating energy company in modern conditions - P. M. Zaitseva; N. G. Lyubimova; A. S. Flaksman (Вестник университета, 2023)
The article studies the improvement of the production activities of a large electric power company in the Moscow region, Public joint stock company “Mosenergo” (hereinafter referred to as “Mosenergo”) by proposing a set of measures for a radical renovation (reengineering) of the main technological business process – “Heat and electricity production”. Based on the process approach and methods of strategic analysis, SWOT (strengths, weaknesses, opportunities, threats), the key company success factors were identified, an enlarged business model of “Mosenergo” was built and analysed, followed by the selection of the most preferable business process. With the help of a matrix of criteria, an assessment of business process importance or readiness for the implementation of the selected strategies was made. Key success factors for “Production of heat and electricity” business process were formed. However, in modern conditions, due to the tightening of sanctions imposed by unfriendly countries, the risks of supply disruptions and termination of equipment maintenance are increasing, which causes negative trends in key performance indicators of the selected business process, namely the accident rate and/or the frequency of emergency operation of automatics cases. The set of measures for reengineering the business process “Production of heat and electricity” is based on the idea of automatic technological business process of the company through the introduction of highly effective domestic digital technologies as part of the industry’s digital transformation strategy. The import substitution programme to minimise risks caused by geopolitical events in the world is considered.